The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1080/22221751.2020.1868274
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pathogenicity and environmental transmission of recent highly pathogenic avian influenza H5 viruses

Abstract: Strategies to control spread of highly pathogenic avian influenza (HPAI) viruses by wild birds appear limited, hence timely characterization of novel viruses is important to mitigate the risk for the poultry sector and human health. In this study we characterize three recent H5-clade 2.3.4.4 viruses, the H5N8-2014 group A virus and the H5N8-2016 and H5N6-2017 group B viruses. The pathogenicity of the three viruses for chickens, Pekin ducks and Eurasian wigeons was compared. The three viruses were highly pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
56
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 51 publications
8
56
0
Order By: Relevance
“…Virus shedding from the infected Anatidae was mainly observed via the oral route as in previous experimental infection studies of Anatidae (Eurasian wigeons and mallards) and clade 2.3.4.4b and 2.3.4.4c H5 HPAIVs [14,20]. Further, two Eurasian wigeons shed virus into the cloaca in late phase of infection.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Virus shedding from the infected Anatidae was mainly observed via the oral route as in previous experimental infection studies of Anatidae (Eurasian wigeons and mallards) and clade 2.3.4.4b and 2.3.4.4c H5 HPAIVs [14,20]. Further, two Eurasian wigeons shed virus into the cloaca in late phase of infection.…”
Section: Discussionsupporting
confidence: 51%
“…Several groups have examined pathogenicity of clade 2.3.4.4c (Group A) H5N2 or H5N8 HPAIVs, which circulated worldwide in 2014-2015, in Anatidae such as the American black duck (Anas rubripes), Baikal teal (Anas formosa), common teal (Anas crecca), Eurasian wigeon, lesser scaup (Aythya a nis), mallard, Mandarin duck (Aix galericulata), pintail, ruddy duck (Oxyura jamaicensis), and surf scoter (Melanitta perspicillata) [14][15][16][17][18][19][20][21][22][23]. Most studies showed that clade 2.3.4.4c HPAIVs caused subclinical infection in Anatidae, and that the viruses were mainly shed via the oral route.…”
mentioning
confidence: 99%
“…Additionally, genetic analysis demonstrated that H5N8 viruses in the 2014–2016 outbreak was likely to transmit from wild birds to domestic ducks, and this played a central role in virus spread to domestic poultry [ 13 , 27 ]. A recent study about comparative pathogenicity of HPAI H5 viruses in Netherland also suggested that virus shedding of duck species including both domestic and wild ducks might increase transmission to the poultry sector [ 28 ]. Collectively, our results in ducks, as well as previous findings concerning Korean HPAI outbreaks, indicate that domestic ducks play an important role in transmission of H5N8 HPAI viruses in the field.…”
Section: Resultsmentioning
confidence: 99%
“…Virus infection has always been a threat to human and animal health. Typical viruses include hepatitis B virus [ 1 ], influenza virus [ 2 ], human immunodeficiency virus (HIV) [ 3 ], and coronavirus [ 4 ], etc., which can cause severe disease. Therefore, antiviral drug development is a major research direction for scientists.…”
Section: Introductionmentioning
confidence: 99%